Karakterisasi Sinyal Sensor Piezoelektrik Komposit Nano Serat akibat Tumbukan Balistik - Ananda Maulana Putra Sanjaya; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
This study investigates the characterization and operational mechanism of piezoelectric sensors based on nanofiber composites under high-velocity impact conditions. These sensors utilize the direct piezoelectric effect of PVDF and its copolymer P(VDF-TrFE), enhanced with inorganic nanofillers such as ZnO, BaTiO₃, and CNTs. Through the electrospinning process, nanoscale fibers with molecular chains aligned to the electric field are produced, promoting the formation of the β-phase and enhancing spontaneous polarization. A systematic literature analysis reveals that the addition of nanofillers significantly increases the piezoelectric coefficient (d₃₃), signal amplitude, and overall sensor sensitivity to dynamic deformation. However, variations in electrode configuration, fiber orientation, filler concentration, and testing methodology lead to discrepancies in quantitative results across studies. Furthermore, explicit Finite Element Method (FEM) modeling is employed to understand the stress-wave propagation and the time-resolved conversion of mechanical to electrical energy. The integration of experimental and numerical approaches proves effective for reconstructing sensor responses under ballistic impact, paving the way for the development of faster, more sensitive, and adaptive impact detection systems in future smart structural applications.